2015
DOI: 10.2172/1235837
|View full text |Cite
|
Sign up to set email alerts
|

Rod internal pressure quantification and distribution analysis using Frapcon

Abstract: This report documents work performed supporting the Department of Energy (DOE) Office of Nuclear Energy (NE) Fuel Cycle Technologies Used Fuel Disposition Campaign (UFDC) under work breakdown structure element 1.02.08.10, ST Analysis. In particular, this report fulfills the M4 milestone M4FT-15OR0810036, Quantify effects of power uncertainty on fuel assembly characteristics, within work package FT-15OR081003-ST Analysis-ORNL. This research was also supported by the Consortium for Advanced Simulation of Light W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The calculations documented in Ref. 21 were consistent with the database documented in Ref. 20 for standard PWR fuel rods.…”
Section: Relevant Ranges Of Internal Pressures and Hoop Stressessupporting
confidence: 78%
See 1 more Smart Citation
“…The calculations documented in Ref. 21 were consistent with the database documented in Ref. 20 for standard PWR fuel rods.…”
Section: Relevant Ranges Of Internal Pressures and Hoop Stressessupporting
confidence: 78%
“…Characterization of the sister rods will result in up to 25 valuable data points for EOL RIP for standard PWR fuel rods. In addition, Oak Ridge National Laboratory used FRAPCON to predict gas pressures for over 68,000 fuel rods irradiated during Cycles 1−12 in the Watts Bar Nuclear Unit 1 reactor [21]. The calculations documented in Ref.…”
Section: Relevant Ranges Of Internal Pressures and Hoop Stressesmentioning
confidence: 99%
“…Pin internal pressurisation was neglected as this was considered a secondary effect. This was because fission gas release was assumed to be low during early fuel cycles not exposed to accident conditions; Bratton et al have shown that the rod internal pressure reaches no more than 6-7 MPa by end of life [49]. Given that the mechanical response is of concern here, a simple linear temperature profile was applied as a boundary condition to the nodes.…”
Section: Test Geometry Loads and Boundary Conditionsmentioning
confidence: 99%
“…With two additional stretch goals: 1) compare results to FRAPCON results obtained by Ryan Bratton [16], a student at Pennsylvania State University working remotely from ORNL, who obtained these results as part of his thesis work; and 2) perform a mesh sensitivity study to assess appropriate refinement level.…”
Section: Milestone Objectivesmentioning
confidence: 99%